Metabolic profile response to administration of epigallocatechin-3-gallate in high-fat-fed mice - Moreno, Mayara Franzoi; De Laquila, Rachel; Okuda, Marcos Hiromu; Lira, Fabio Santos [UNESP]; Morais Honorato de Souza, Gabriel Inacio de; Souza, Claudio Teodoro de; Telles, Monica Marques; Ribeiro, Eliane Beraldi; Oller do Nascimento, Claudia Maria; Oyama, Lila Missae (Biomed Central Ltd, 2014)
Background: Obesity is associated with increased adipose tissue and glucose intolerance. High-fat diets (HFDs) are known to induce obesity and increase proinflammatory adipokines. The consumption of green tea may improve the health of obese individuals because it contains a potent antioxidant that has effects on body weight, energy expenditure and serum cholesterol concentrations.Methods: We examined the effects of epigallocatechin-3-gallate (EGCG) (50 mg/kg body weight per day) or saline after 30 or 60 days of treatment. Mice were distributed into four groups: 1) NS: normolipidic diet receiving saline; 2) NE: normolipidic diet receiving EGCG; 3) HFS: high-fat diet receiving saline; 4) HFE: high-fat diet receiving EGCG.Results: We observed that administration of a HFD plus EGCG treatment for 60 days reduced delta weight, the relative weights of the mesenteric adipose tissue (MES), retroperitonial adipose tissue (RET), epididymal adipose tissue (EPI), the sum of the adipose tissues (SAT), reduced triacylglycerol (TG) and improved both high-density lipoprotein (HDL) cholesterol levels and the adiponectin/STA ratio when compared with HFS.Conclusions: Our results suggest that the chronic administration of EGCG (60 days) promoted a significant improvement in glucose tolerance, decreased adipose tissue deposits, weight mass, TG and HDL-C only when associated with high-fat diet treatment.
Keywords: High-fat diet; Adipokines; Adipose tissue; Inflammation